By mimicking the proof of Theorem 3.4, convert the following second-order differential equations into first-order systems and use matrix exponentials to solve them. a. y __ (t) y _ (t) 2y(t) = 0, y(0) = 1, y _ (0) = 4 b. y __ (t) 2y _ (t) + y(t) = 0, y(0) = 1, y _ (0) = 2

\}J.f-I 8 ;/rrtth.dJ. edw 0fa-ce.c t.e hllb-e"of ~t()f5 1VIL h a.z(f--lll1-jti-e . Ueitor: 2ff lLis. fhoh.aJ2.thrL th0:1+~ e.-tor;..fJtih•. {MAfi~1~ 5 _t3_Jlfi-fDr.5~ ic1LLft/,~ ~ t-7 P'1J:t-lA.:k_ rx.:2.et0 +,,4fJiJ,.'Ob tf.cIt --~z:.;fJ'51J2M...